MAPPING OF DIVORCE-PRONE AREAS BASED ON GEOGRAPHIC INFORMATION SYSTEM - Moch Tohet; Muhammad Zainuddin Sunarto (JURNAL HAKAM, 2023)
The research aims to determine the location points prone to divorce in the Kraksaan District Court with the Geographic Information System application so that it can make it easier for the Kraksaan Religious Court officers to make decisions and make it easier for all people and admins in particular. The research method used in this study combines qualitative and quantitative methods. Qualitative methods are used in data collection using literature studies and observations. At the same time, the quantitative method is tested to obtain conclusions in developing this research system, namely using the waterfall method with the stages of analysis, design and coding. The study results show that: the geographic information system-based mapping application of divorce-prone areas is very effective in identifying areas that require special attention in resolving divorce cases. The information obtained from this application helps the court to direct prevention, counselling and mediation efforts in areas prone to divorce, as well as to optimize the allocation of resources and support programs accordingly.